2002
DOI: 10.1093/geronb/57.1.p87
|View full text |Cite
|
Sign up to set email alerts
|

Negative Life Events and Depression in Elderly Persons: A Meta-Analysis

Abstract: In a meta-analysis of 25 studies, the relationship of both specific types of negative life events and the total number of experienced events to depression in old age was studied. Almost all negative life events appeared to have a modest but significant relationship with depression. The total number of negative life events and the total number of daily hassles appeared to have the strongest relationship with depression (respectively, combined r =.15, n = 5,037, and combined r =.41, n = 461), whereas sudden unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
197
3
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(244 citation statements)
references
References 52 publications
26
197
3
5
Order By: Relevance
“…The association between negative early life events and later life mental health problems is well documented in the literature. Numerous studies have shown that adult mental health consequences of negative early life events-such as childhood abuse, death of a parent and poor socioeconomic circumstances-include depression, anxiety disorders and substance abuse (Springer et al 2003;Arnow 2004;Batten et al 2004;Draper et al 2008;Kraaij et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The association between negative early life events and later life mental health problems is well documented in the literature. Numerous studies have shown that adult mental health consequences of negative early life events-such as childhood abuse, death of a parent and poor socioeconomic circumstances-include depression, anxiety disorders and substance abuse (Springer et al 2003;Arnow 2004;Batten et al 2004;Draper et al 2008;Kraaij et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Major life events such as widowhood are also associated with a disturbance in one's normal routine (including participation in health behaviors) and an increase in stress (Holmes & Rahe, 1967). A recent meta-analysis found that total life events as well as the death of significant others were associated with higher levels of depressive symptoms in older adults (Kraaij, Arensman, & Spinhoven, 2002). Depression, in turn, has been shown to interfere with health behaviors and compliance with medical treatment (DiMatteo, Lepper, & Croghan, 2000).…”
mentioning
confidence: 99%
“…However, research has reported that negative life events alone only account for a relatively modest percentage of the variance in depression [1,2]. This indicates that other variables may contribute to the relationship between negative life events and depression.…”
Section: Introductionmentioning
confidence: 98%